Clinicopathologic characteristics and prognosis of upper tract urothelial carcinoma complicated with aristolochic acid nephropathy after radical nephroureterectomy - Hongli Shan; Wen Tian; Yazhao Hong; Bo Xu; Chunxi Wang; Bing Yu; Xiaoqing Wang (BMC, 2020)
Abstract Background The purpose of this study was to identify the clinicopathologic characteristics and prognosis of upper tract urothelial carcinoma (UTUC) patients complicated with aristolochic acid nephropathy(AAN) after radical nephroureterectomy (RNU). Methods The clinical data of 42 UTUC patients with AAN (AAN group) and 238 UTUC patients without AAN (Non-AAN group) were retrospectively reviewed. All patients received a RNU with excision of bladder cuff. Demographic and clinical data, including preoperative indexes, intraoperative indexes and surgical outcomes were compared. Results There were no significant differences in age, tumor location, surgery approach, tumor pathologic grade, stage, the mean operative time and estimated blood loss between the two groups (all p > 0.05). There were more female patients in the AAN group (p < 0.001), and 57.1% were high grade tumors. The AAN group showed a higher complications rate (p = 0.003). The median follow-up time was 43.2 months. The AAN group showed a worse estimated 5-year overall survival rate (35.1% vs. 63.0%, p = 0.014), however, no significant difference was found between the two groups with regard to disease specific survival (63.5% vs. 81.5%, p = 0.091). Multivariate binary logistic regression analysis showed that AAN was an independent factor related with overall and disease specific survival. 38.9% of all patients experienced any types of recurrence, and the estimated 5-year recurrence-free survival rate was lower in the AAN group (37.1% vs. 63.7%, p = 0.001). In the comparison of subgroups stratified by recurrence type, the AAN group had a higher intravesical (p = 0.030) and contralateral recurrence rate (p = 0.040). Conclusion UTUC with AAN occurred more frequently in female patients who were more likely to develop high-grade tumors. However, these patients showed a worse overall survival and a lower recurrence-free survival rate than the other patients. AA-related UTUC might be associate with an increased risk of intravesical and contralateral recurrence after RUN.